ERG induces taxane resistance in castration-resistant prostate cancer - Galletti, Giuseppe (Nat Commun, 2014)
Taxanes are the only chemotherapies used to treat patients with metastatic castration-resistant prostate cancer (CRPC). Despite the initial efficacy of taxanes in treating CRPC, all patients ultimately fail due to the development of drug resistance. In this study, we show that ERG overexpression in in vitro and in vivo models of CRPC is associated with decreased sensitivity to taxanes. ERG affects several parameters of microtubule dynamics and inhibits effective drug-target engagement of docetaxel or cabazitaxel with tubulin. Finally, analysis of a cohort of 34 men with metastatic CRPC treated with docetaxel chemotherapy reveals that ERG-overexpressing prostate cancers have twice the chance of docetaxel resistance than ERG-negative cancers. Our data suggest that ERG plays a role beyond regulating gene expression and functions outside the nucleus to cooperate with tubulin towards taxane insensitivity. Determining ERG rearrangement status may aid in patient selection for docetaxel or cabazitaxel therapy and/or influence co-targeting approaches.